Analysis of mitotic microtubule-associated proteins using mass spectrometry identifies astrin, a spindle-associated protein - Mack, Gary J. (The National Academy of Sciences, 2001)
We purified microtubules from a mammalian mitotic extract and obtained an amino acid sequence from each microtubule-associated protein by using mass spectrometry. Most of these proteins are known spindle-associated components with essential functional roles in spindle organization. We generated antibodies against a protein identified in this collection and refer to it as astrin because of its association with astral microtubule arrays assembled in vitro. Astrin is ≈134 kDa, and except for a large predicted coiled-coil domain in its C-terminal region it lacks any known functional motifs. Astrin associates with spindle microtubules as early as prophase where it concentrates at spindle poles. It localizes throughout the spindle in metaphase and anaphase and associates with midzone microtubules in anaphase and telophase. Astrin also localizes to kinetochores but only on those chromosomes that have congressed. Deletion analysis indicates that astrin's primary spindle-targeting domain is at the C terminus, although a secondary domain in the N terminus can target some of the protein to spindle poles. Thus, we have generated a comprehensive list of major mitotic microtubule-associated proteins, among which is astrin, a nonmotor spindle protein.